Euphemistic strategies in Algerian Arabic and American English - Alghazo Sharif; Bekaddour Soumia; Jarrah Marwan; Hammouri Yazeed (ExELL (Explorations in English Language and Linguistics))
This study aims to explore the use of euphemistic strategies by Algerians and Americans when dealing with three unpleasant topics: death, lying, and disease. It also examines the effect of degree of formality on the use of euphemistic strategies. To achieve this objective, a discourse completion task (DCT) was distributed to 21 Algerians and 21 Americans. The data were analysed using SPSS. The data analysis revealed that there are some differences and similarities between the two groups. The euphemistic strategies used by the Americans when they deal with death topics are synonyms and part for the whole. The Algerians use part for the whole, overstatement, and synonyms when they deal with death. Regarding the topic of lying, the Americans employ strategies of understatement and deletion, whereas the Algerians use understatement and metaphor. As for the topic of disease, the Americans use vagueness, and the Algerians use vagueness, metaphor, and deletion. These findings reveal that both groups resort to euphemism when dealing with these three unpleasant topics. However, their use of euphemistic strategies is culture-bound.